Aerodynamic losses and endwall heat transfer in a linear vane cascade with endwall film-cooling and endwall-leading edge contouring - Mahmood, Gazi (University of Pretoria, 2019)
Thesis (PhD (Mechanical Engineering))--University of Pretoria, 2019.